How to conduct surveys : a step-by-step guide - Arlene Fink (SAGE Publications, 2013)
"The Fifth Edition of the best-selling How to Conduct Surveys guides readers through the process of developing their own rigorous surveys and evaluating the credibility of surveys created by others. Offering practical, step-by-step advice and written in the same clear and accessible style as her other works, author Arlene Fink centers her guidance on choosing the appropriate type of survey, writing survey questions and responses, formatting the survey, deciding on the characteristics and numbers of respondents to include, determining the frequency of surveying respondents, and analyzing and reporting the results. The Fifth Edition pays particular attention to the internet and online surveys, considering best practices and techniques for developing a thorough and effective survey. "--Publisher.